Near-resonance in a System of Sub-Neptunes from TESS - Quinn, Samuel N.; Becker, Juliette C.; Rodriguez, Joseph E.; Hadden, Sam; Huang, Chelsea X.; Morton, Timothy D.; Adams, Fred C.; Armstrong, David; Eastman, Jason D.; Horner, Jonathan; Kane, Stephen R.; Lissauer, Jack J.; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite detection of a multi-planet system orbiting the V = 10.9 K0 dwarf TOI-125. We find evidence for up to five planets, with varying confidence. Three transit signals with high signal-to-noise ratio correspond to sub-Neptune-sized planets (2.76, 2.79, and 2.94 R⊕), and we statistically validate the planetary nature of the two inner planets (Pb = 4.65 days, Pc = 9.15 days). With only two transits observed, we report the outer object (P.03 = 19.98 days) as a planet candidate with high signal-to-noise ratio. We also detect a candidate transiting super-Earth (1.4 R⊕) with an orbital period of only 12.7 hr and a candidate Neptune-sized planet (4.2 R⊕) with a period of 13.28 days, both at low signal-to-noise ratio. This system is amenable to mass determination via radial velocities and transit-timing variations, and provides an opportunity to study planets of similar size while controlling for age and environment. The ratio of orbital periods between TOI-125 b and c (Pc/Pb = 1.97) is slightly lower than an exact 2:1 commensurability and is atypical of multiple planet systems from Kepler, which show a preference for period ratios just wide of first-order period ratios. A dynamical analysis refines the allowed parameter space through stability arguments and suggests that despite the nearly commensurate periods, the system is unlikely to be in resonance.
Keywords: dept.phy; peer-reviewed

Characterization of iron doped zinc oxide nanoparticles using fluorescence spectroscopy - Fernando, M.; Singhal, R.; LeMaire, P.K.; Wu, B. (Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS, 2019)
ZnO and Fe-doped ZnO nanoparticles were analyzed in ethanol solution and dry powder form using fluorescence spectroscopy. Near-band-edge emission (NBE) and defect emission (DE) peaks were studied. A blue-shift was observed with the NBE emission peak. © OSA 2019. The Author(s).
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS
Keywords: Blue shift; Defect emission; Dry powders; Emission peaks; Ethanol solutions; Fe-doped; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron oxides; Iron-doped; Nanoparticles; Near band edge emissions; Oxide minerals; Zinc oxide; ZnO nanoparticles; dept.phy

Thin Film Deposition and Carbon Nanotube Synthesis - Frey, J.; Schwendemann, T.C. (International Journal of High Speed Electronics and Systems, 2019)
Carbon nanotubes (CNTs) are a viable product for many different markets. One specific area of promise is the use of CNTs in supercapacitors. The CNT synthesis is a two-step process with the first being the formation of a thin film layer. The thin film substrate is created by means of the Thermal Evaporation Physical Vapor Deposition (TPVD) process. After the thin film substrate is deposited, the CNTs are grown in a Chemical Vapor Deposition (CVD) growth chamber. Analysis of the thin film substrate and CNTs is performed primarily using Scanning Electron Microscopy (SEM). The results show the inclusion of ultrapure water in the CVD process contributed to the success of CNT growth. Multiple prong CNT grow is seen for CVDs trails of silver thin film layer deposited on silicon substrates. The silver nanoparticle had a large diameter with an acute contact angle. The single prong growth indicates the iron nanoparticles formed an obtuse contact angle due to the amorphic surface of alumina substrate. The focus of this project is to explore and investigate different materials and conditions for optimal CNT synthesis in the hopes of creating a uniform forest of vertically aligned carbon nanotubes. © 2019 World Scientific Publishing Company.
0 citations (Crossref) [2023-10-31]
Keywords: Alumina; Alumina substrates; Aluminum oxide; Carbon nanotube synthesis; Carbon nanotubes; Chemical vapor deposition; Chemical vapor depositions (CVD); Contact angle; Iron nanoparticles; Nanoparticles; Physical vapor deposition; Scanning electron microscopy; Silicon substrates; Silver nanoparticles; Substrates; Thermal evaporation; Thin film substrate; Thin films; Thin-film depositions; Vertically aligned carbon nanotube; dept.phy; peer-reviewed

Breast cancer diagnosis using fluorescence spectroscopy with dualwavelength excitation and machine learning - Gaoa, X.; Wu, B. (Progr. Biomed. Opt. Imaging Proc. SPIE, 2019)
Intrinsic fluorescence spectra of fresh normal and cancerous human breast tissues were measured using two selective excitation wavelengths including 290nm and 340nm. Dual-wavelength excitation may reveal more molecular information than single-wavelength excitation. In the meantime, it is significantly faster than the acquisition of excitation-emission (EEM) matrix. Unsupervised machine learning algorithms principal component analysis (PCA) and non-negative matrix factorization (NMF) were used to reduce the dimensionality of the spectral data. The relative concentrations of the basis spectra retrieved by PCA and NMF were considered features of the samples and used to distinguish normal and malignant tissues. The performances of classification using support vector machine (SVM) based on PCA and NMF features were compared. The classification using spectral data with dual-wavelength excitation was compared with single-wavelength excitation. Classification based on NMF-retrieved components from spectral data with dual-wavelength excitation yielded the best performance. © 2019 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Progr. Biomed. Opt. Imaging Proc. SPIE
Keywords: Biopsy; Breast Cancer; Breast cancer; Cancer diagnosis; Classification (of information); Diseases; Dual wavelength; Dual-wavelength excitation; Factorization; Fluorescence; Fluorescence spectroscopy; Histology; Learning algorithms; Machine learning; Matrix algebra; Nonnegative matrix factorization; Optical biopsies; Optical biopsy; Principal component analysis; Support vector machine; Support vector machines; Tissue; dept.phy

Centrality and transverse momentum dependence of D0 -meson production at mid-rapidity in Au + Au collisions at s NN =200 GeV - STAR Collaboration (Physical Review C, 2019)
We report a new measurement of D0-meson production at mid-rapidity (|y|<1) in Au + Au collisions at sNN=200GeV utilizing the heavy flavor tracker, a high resolution silicon detector at the STAR experiment. Invariant yields of D0 mesons with transverse momentum pT9GeV/c are reported in various centrality bins (0-10%, 10-20%, 20-40%, 40-60%, and 60-80%). Blast-wave thermal models are used to fit the D0-meson pT spectra to study D0 hadron kinetic freeze-out properties. The average radial flow velocity extracted from the fit is considerably smaller than that of light hadrons (π,K, and p), but comparable to that of hadrons containing multiple strange quarks (φ,Ξ-), indicating that D0 mesons kinetically decouple from the system earlier than light hadrons. The calculated D0 nuclear modification factors reaffirm that charm quarks suffer a large amount of energy loss in the medium, similar to those of light quarks for pT>4GeV/c in central 0-10% Au + Au collisions. At low pT, the nuclear modification factors show a characteristic structure qualitatively consistent with the expectation from model predictions that charm quarks gain sizable collective motion during the medium evolution. The improved measurements are expected to offer new constraints to model calculations and help gain further insights into the hot and dense medium created in these collisions. © 2019 American Physical Society.
44 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetry for inclusive jet and dijet production in pp collisions at s =510 GeV - STAR Collaboration (Physical Review D, 2019)
We report the first measurement of the inclusive jet and the dijet longitudinal double-spin asymmetries, ALL, at midrapidity in polarized pp collisions at a center-of-mass energy s=510 GeV. The inclusive jet ALL measurement is sensitive to the gluon helicity distribution down to a gluon momentum fraction of x≈0.015, while the dijet measurements, separated into four jet-pair topologies, provide constraints on the x dependence of the gluon polarization. Both results are consistent with previous measurements made at s=200 GeV in the overlapping kinematic region, x>0.05, and show good agreement with predictions from recent next-to-leading order global analyses. © 2019 authors. Published by the American Physical Society.
26 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurement of inclusive J/ψ suppression in Au+Au collisions at sNN=200 GeV through the dimuon channel at STAR - STAR Collaboration (Physics Letters, Section B: Nuclear, Elementary Particle and High-Energy Physics, 2019)
J/ψ suppression has long been considered a sensitive signature of the formation of the Quark-Gluon Plasma (QGP) in relativistic heavy-ion collisions. In this letter, we present the first measurement of inclusive J/ψ production at mid-rapidity through the dimuon decay channel in Au+Au collisions at sNN=200 GeV with the STAR experiment. These measurements became possible after the installation of the Muon Telescope Detector was completed in 2014. The J/ψ yields are measured in a wide transverse momentum (pT) range of 0.15 GeV/c to 12 GeV/c from central to peripheral collisions. They extend the kinematic reach of previous measurements at RHIC with improved precision. In the 0-10% most central collisions, the J/ψ yield is suppressed by a factor of approximately 3 for pT>5 GeV/c relative to that in p+p collisions scaled by the number of binary nucleon-nucleon collisions. The J/ψ nuclear modification factor displays little dependence on pT in all centrality bins. Model calculations can qualitatively describe the data, providing further evidence for the color-screening effect experienced by J/ψ mesons in the QGP. © 2019 The Author(s)
18 citations (Crossref) [2023-10-31]
Keywords: Color-screening; J/ψ suppression; Quark-gluon plasma; dept.phy; peer-reviewed

Measurement of the longitudinal spin asymmetries for weak boson production in proton-proton collisions at s =510 GeV - STAR Collaboration (Physical Review D, 2019)
We report new STAR measurements of the single-spin asymmetries AL for W+ and W- bosons produced in polarized proton-proton collisions at s=510 GeV as a function of the decay-positron and decay-electron pseudorapidity. The data were obtained in 2013 and correspond to an integrated luminosity of 250 pb-1. The results are combined with previous results obtained with 86 pb-1. A comparison with theoretical expectations based on polarized lepton-nucleon deep-inelastic scattering and prior polarized proton-proton data suggests a difference between the ū and d quark helicity distributions for 0.05<x<0.25. In addition, we report new results for the double-spin asymmetries ALL for W±, as well as AL for Z/γ∗ production and subsequent decay into electron-positron pairs. © 2019 authors. Published by the American Physical Society.
20 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Measurements of the transverse-momentum-dependent cross sections of J /ψ production at mid-rapidity in proton+proton collisions at s =510 and 500 GeV with the STAR detector - STAR Collaboration (Physical Review D, 2019)
We present measurements of the differential cross sections of inclusive J/ψ meson production as a function of transverse momentum (pTJ/ψ) using the μ+μ- and e+e- decay channels in proton+proton collisions at center-of-mass energies of 510 and 500 GeV, respectively, recorded by the STAR detector at the Relativistic Heavy Ion Collider. The measurement from the μ+μ- channel is for 0<pTJ/ψ<9 GeV/c and rapidity range |yJ/ψ|<0.4, and that from the e+e- channel is for 4<pTJ/ψ<20 GeV/c and |yJ/ψ|<1.0. The ψ(2S) to J/ψ ratio is also measured for 4<pTmeson<12 GeV/c through the e+e- decay channel. Model calculations, which incorporate different approaches toward the J/ψ production mechanism, are compared with experimental results and show reasonable agreement within uncertainties. © 2019 authors. Published by the American Physical Society.
8 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

STAR Collaboration - STAR Collaboration (Nuclear Physics A, 2019)
1 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (International Journal of High Speed Electronics and Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Preface - Jain, F.; Broadbridge, C.; Gherasimova, M.; Tang, H. (High Performance Logic and Circuits for High-Speed Electronic Systems, 2019)
0 citations (Crossref) [2023-10-31]
Keywords: dept.phy

Three Red Suns in the Sky: A Transiting, Terrestrial Planet in a Triple M-dwarf System at 6.9 pc - Winters, J.G.; Medina, A.A.; Irwin, J.M.; Charbonneau, D.; Astudillo-Defru, N.; Horch, E.P.; Eastman, J.D.; Vrijmoet, E.H.; Henry, T.J.; Diamond-Lowe, H.; Winston, E.; Barclay, T.; et al. (Astronomical Journal, 2019)
We present the discovery from Transiting Exoplanet Survey Satellite (TESS) data of LTT 1445Ab. At a distance of 6.9 pc, it is the second nearest transiting exoplanet system found to date, and the closest one known for which the primary is an M dwarf. The host stellar system consists of three mid-to-late M dwarfs in a hierarchical configuration, which are blended in one TESS pixel. We use MEarth data and results from the Science Processing Operations Center data validation report to determine that the planet transits the primary star in the system. The planet has a radius of, an orbital period of days, and an equilibrium temperature of K. With radial velocities from the High Accuracy Radial Velocity Planet Searcher, we place a 3σ upper mass limit of 8.4 on the planet. LTT 1445Ab provides one of the best opportunities to date for the spectroscopic study of the atmosphere of a terrestrial world. We also present a detailed characterization of the host stellar system. We use high-resolution spectroscopy and imaging to rule out the presence of any other close stellar or brown dwarf companions. Nineteen years of photometric monitoring of A and BC indicate a moderate amount of variability, in agreement with that observed in the TESS light-curve data. We derive a preliminary astrometric orbit for the BC pair that reveals an edge-on and eccentric configuration. The presence of a transiting planet in this system hints that the entire system may be co-planar, implying that the system may have formed from the early fragmentation of an individual protostellar core. © 2019. The American Astronomical Society. All rights reserved..
55 citations (Crossref) [2023-10-31]
Keywords: binaries: close; dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (LTT 1445); stars: low-mass

Human brain glioma grading using label free laser-induced fluorescence spectroscopy - Zhou, Y.; Liu, C.-H.; Zhu, K.; Wu, B.; Yu, X.; Cheng, G.; Zhao, M.; Zong, R.; Zhang, C.; Chen, H.; Li, S.; Liang, Q.; et al. (Progr. Biomed. Opt. Imaging Proc. SPIE, 2019)
Laser-induced fluorescence (LIF) technique was used to generate spectral signatures of endogenous fluorophores relevant to the tissue molecular composition changes in human brain glioma tumors. The goal is to study the changes of fluorescence emission spectra from endogenous fluorophores in human brain glioma of different grades, and to find new biomarkers for prognostic optical molecular pathological diagnosis. Two hundred and thirty-seven (237) native fluorescence spectra from 61 subjects were measured using LabRAM HR Evolution micro photoluminescence (PL) system for four grades of glioma tumors in ex-vivo. The differences of four grades of glioma tumors were identified by the characteristic fluorophores fingerprints under the excitation laser wavelength at UV 325nm. To our best knowledge, this is the first report for human brain study using this technique. The fluorescence peaks of biomarkers with major contribution were found, including tryptophan, collagen, elastin, reduced nicotinamide adenine dinucleotide (NADH), flavin adenine dinucleotide (FAD) and phospholipids that play important roles in the cellular energy metabolism and glycolysis pathway. The ratios of peak intensities and the peak positions in fluorescence spectra of may be used to diagnose human brain diseases or to guide biopsy during surgical resection. © 2019 SPIE.
0 citations (Crossref) [2023-10-31] Journal Abbreviation: Progr. Biomed. Opt. Imaging Proc. SPIE
Keywords: Amino acids; Biomarkers; Biopsy; Brain; Cellular energy; Cellular energy metabolism; Emission spectroscopy; FAD; Fluorescence; Fluorescence microscopy; Fluorescence spectroscopy; Fluorophores; Grading; Human brain; Human brain glioma tissues; Laser excitation; Laser induced fluorescence spectroscopy; Laser optics; Laser produced plasmas; Metabolism; NADH; Native fluorescence; Native laser-induced fluorescence spectroscopy; Native-fluorescence; Nucleotides; Optical molecular pathology; Pathology; Phospholipids; Tryptophan; Tumors; dept.phy

A portable visible resonance Raman analyzer with a handheld optical fiber probe for in vivo diagnosis of brain glioblastoma multiforme in an animal model - Zhou, Y.; Zhang, S.; Wu, B.; Yu, X.; Cheng, G.; Zhu, K.; Zhao, M.; Zheng, J.; Zhang, M.; Liang, Q.; Liu, C.-H.; Alfano, R.R. (Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS, 2019)
A VRR-LRR analyzer with handheld fiber‐optic probe is reported for the first time for diagnosis of brain GBM in vivo. The sensitivity for identification is 80% compared with histopathology examination. © OSA 2019. The Author(s).
2 citations (Crossref) [2023-10-31] Journal Abbreviation: Front. Opt. - Proc. Front. Opt. Laser Sci. APS/DLS
Keywords: Animal model; Fiberoptic probes; Glioblastoma multiforme; Handhelds; In-vivo; Optical fiber probe; Optical fibers; Probes; Resonance Raman; dept.phy

Polarization of Λ (Λ ̄) Hyperons along the Beam Direction in Au+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2019)
The Λ (Λ̄) hyperon polarization along the beam direction has been measured in Au+Au collisions at sNN=200 GeV, for the first time in heavy-ion collisions. The polarization dependence on the hyperons' emission angle relative to the elliptic flow plane exhibits a second harmonic sine modulation, indicating a quadrupole pattern of the vorticity component along the beam direction, expected due to elliptic flow. The polarization is found to increase in more peripheral collisions, and shows no strong transverse momentum (pT) dependence at pT greater than 1 GeV/c. The magnitude of the signal is about 5 times smaller than those predicted by hydrodynamic and multiphase transport models; the observed phase of the emission angle dependence is also opposite to these model predictions. In contrast, the kinematic vorticity calculations in the blast-wave model tuned to reproduce particle spectra, elliptic flow, and the azimuthal dependence of the Gaussian source radii measured with the Hanbury Brown-Twiss intensity interferometry technique reproduce well the modulation phase measured in the data and capture the centrality and transverse momentum dependence of the polarization signal. © 2019 American Physical Society.
100 citations (Crossref) [2023-10-31]
Keywords: Azimuthal dependence; Colliding beam accelerators; Emission angle dependence; Gaussian beams; Heavy ion collision; Heavy ions; Hyperon polarization; Interferometry; Interferometry technique; Modulation; Multiphase transport; Polarization; Polarization dependence; Polarization signals; Vorticity; dept.phy; peer-reviewed

First Observation of the Directed Flow of D0 and D0 ̄ in Au+Au Collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2019)
We report the first measurement of rapidity-odd directed flow (v1) for D0 and D0̄ mesons at midrapidity (|y|<0.8) in Au+Au collisions at sNN=200 GeV using the STAR detector at the Relativistic Heavy Ion Collider. In 10-80% Au+Au collisions, the slope of the v1 rapidity dependence (dv1/dy), averaged over D0 and D0̄ mesons, is -0.080±0.017(stat)±0.016(syst) for transverse momentum pT above 1.5 GeV/c. The absolute value of D0 meson dv1/dy is about 25 times larger than that for charged kaons, with 3.4σ significance. These data give a unique insight into the initial tilt of the produced matter, and offer constraints on the geometric and transport parameters of the hot QCD medium created in relativistic heavy-ion collisions. © 2019 American Physical Society.
47 citations (Crossref) [2023-10-31]
Keywords: Absolute values; Au+Au collisions; Bosons; Colliding beam accelerators; Directed flow; Germanium compounds; Gold compounds; Hadrons; Heavy ions; Mid-rapidity; Relativistic Heavy Ion Collider; Relativistic heavy ion collision; Transport parameters; Transverse momenta; dept.phy; peer-reviewed

Observation of Excess J /ψ Yield at Very Low Transverse Momenta in Au+Au Collisions at sNN =200 GeV and U+ U Collisions at sNN =193 GeV - STAR Collaboration (Physical Review Letters, 2019)
We report on the first measurements of J/ψ production at very low transverse momentum (pT<0.2 GeV/c) in hadronic Au+Au collisions at sNN=200 GeV and U+U collisions at sNN=193 GeV. Remarkably, the inferred nuclear modification factor of J/ψ at midrapidity in Au+Au (U+U) collisions reaches about 24 (52) for pT<0.05 GeV/c in the 60%-80% collision centrality class. This noteworthy enhancement cannot be explained by hadronic production accompanied by cold and hot medium effects. In addition, the dN/dt distribution of J/ψ for the very low pT range is presented for the first time. The distribution is consistent with that expected from the Au nucleus and shows a hint of interference. Comparison of the measurements to theoretical calculations of coherent production shows that the excess yield can be described reasonably well and reveals a partial disruption of coherent production in semicentral collisions, perhaps due to the violent hadronic interactions. Incorporating theoretical calculations, the results strongly suggest that the dramatic enhancement of J/ψ yield observed at extremely low pT originates from coherent photon-nucleus interactions. In particular, coherently produced J/ψ's in violent hadronic collisions may provide a novel probe of the quark-gluon plasma. © 2019 authors. Published by the American Physical Society.
19 citations (Crossref) [2023-10-31]
Keywords: Au+Au collisions; Colliding beam accelerators; Germanium compounds; Gold compounds; Hadronic collisions; Hadronic interactions; Isomers; Nitrogen compounds; Nuclear modification factors; Quark-gluon plasma; Semicentral collisions; Theoretical calculations; Transverse momenta; dept.phy; peer-reviewed

Charge-dependent pair correlations relative to a third particle in p + Au and d + Au collisions at RHIC - STAR Collaboration (Physics Letters B, 2019)
Quark interactions with topological gluon configurations can induce chirality imbalance and local parity violation in quantum chromodynamics. This can lead to electric charge separation along the strong magnetic field in relativistic heavy-ion collisions – the chiral magnetic effect (CME). We report measurements by the STAR collaboration of a CME-sensitive observable in p+Au and d+Au collisions at 200 GeV, where the CME is not expected, using charge-dependent pair correlations relative to a third particle. We observe strong charge-dependent correlations similar to those measured in heavy-ion collisions. This bears important implications for the interpretation of the heavy-ion data.
22 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

A kinematically cold structure of candidate young OB stars toward the anticenter - Casetti-Dinescu, Dana I.; Girard, Terrence M. (The Astrophysical Journal, 2019)
We combine Galaxy Evolution Explorer and Gaia DR2 catalogs to track star formation in the outskirts of our Galaxy. Using photometry, proper motions, and parallaxes we identify a structure of ∼300 OB-type candidates located between 12 and 15 kpc from the Galactic center that are kinematically cold. The structure is located between l =120° and 200°, above the plane up to ∼700 pc and below the plane to ∼1 kpc. The bulk motion is disklike; however, we measure a mean upward vertical motion of 5.7 +0.4 km s-1, and a mean outward radial motion of between 8 and 16 km s-1. The velocity dispersion along the least dispersed of its proper-motion axes (perpendicular to the Galactic disk) is 6.0 +0.3 km s-1, confirming the young age of this structure. While spatially encompassing the outer spiral arm of the Galaxy, this structure is not a spiral arm. Its explanation as the Milky Way warp is equally unsatisfactory. The structure's vertical extent, mean kinematics, and asymmetry with respect to the plane indicate that its origin is more akin to a wobble generated by a massive satellite perturbing the Galaxy's disk. The mean stellar ages in this outer structure indicate the event took place some 200 Myr ago. © 2019. The American Astronomical Society. All rights reserved..
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/153-202-988-565-531, pop00133 tex.type: [object Object]
Keywords: dept.phy

TOI-150b and TOI-163b: two transiting hot Jupiters, one eccentric and one inflated, revealed by TESS near and at the edge of the JWST CVZ - Kossakowski, Diana; Espinoza, Néstor; Brahm, Rafael; Jordán, Andrés; Henning, Thomas; Rojas, Felipe; Kürster, Martin; Sarkis, Paula; Schlecker, Martin; Pozuelos, F. J.; Barkaoui, Khalid; Jehin, Emmanuel; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
We present the discovery of TYC9191-519-1b (TOI-150b, TIC 271893367) and HD271181b (TOI-163b, TIC 179317684), two hot Jupiters initially detected using 30-min cadence Transiting Exoplanet Survey Satellite (TESS) photometry from Sector 1 and thoroughly characterized through follow-up photometry (CHAT, Hazelwood, LCO/CTIO, El Sauce, TRAPPIST-S), high-resolution spectroscopy (FEROS, CORALIE), and speckle imaging (Gemini/DSSI), confirming the planetary nature of the two signals. A simultaneous joint fit of photometry and radial velocity using a new fitting package JULIET reveals that TOI-150b is a 1.254 ± 0.016 RJ, massive (2.61+−001912 MJ) hot Jupiter in a 5.857-d orbit, while TOI-163b is an inflated (RP = 1.478+−00022029 RJ, MP = 1.219 ± 0.11 MJ) hot Jupiter on a P = 4.231-d orbit; both planets orbit F-type stars. A particularly interesting result is that TOI-150b shows an eccentric orbit (e = 0.262+−00045037), which is quite uncommon among hot Jupiters. We estimate that this is consistent, however, with the circularization time-scale, which is slightly larger than the age of the system. These two hot Jupiters are both prime candidates for further characterization – in particular, both are excellent candidates for determining spin-orbit alignments via the Rossiter–McLaughlin (RM) effect and for characterizing atmospheric thermal structures using secondary eclipse observations considering they are both located closely to the James Webb Space Telescope (JWST) Continuous Viewing Zone (CVZ). © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
15 citations (Crossref) [2023-10-31] Citation Key Alias: pop00004 tex.type: [object Object]
Keywords: Planets and satellites: detection; Stars: individual: HD271181; Stars: individual: TIC 179317684; Stars: individual: TIC 271893367; Stars: individual: TYC9191-519-1; Techniques: photometric; dept.phy; peer-reviewed

High-resolution imaging transit photometry of Kepler-13AB - Howell, Steve B.; Scott, Nicholas J.; Matson, Rachel A.; Horch, Elliott P.; Stephens, Andrew (The Astronomical Journal, 2019)
Using the high-resolution imaging instrument, 'Alopeke, at the Gemini-N telescope, we obtained simultaneous two-channel time-series observations of the binary exoplanet host star Kepler13-AB. Our optical observations were obtained during a transit event of the exoplanet Kepler-13b and light curves were produced using both speckle interferometric and aperture photometry techniques. Both techniques confirm that the transiting object orbits the star Kepler-13A while different transit depths are seen across the optical wavelength range, being ∼2 times deeper in the blue. These measurements, as well as mass determinations in the literature, are consistent with Kepler-13b being a highly irradiated gas giant with a bloated atmosphere. Our observations highlight the ability of high-resolution speckle imaging to not only assess binarity in exoplanet host stars but robustly determine which of the stars the transiting object actually orbits. © 2019. The American Astronomical Society. All rights reserved.
10 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/165-359-450-283-875, pop00155 tex.type: [object Object]
Keywords: binaries: close; dept.phy; galaxies: photometry; instrumentation: high angular resolution; peer-reviewed; planetary systems; techniques: image processing

Collision-energy dependence of second-order off-diagonal and diagonal cumulants of net-charge, net-proton, and net-kaon multiplicity distributions in Au + Au collisions - STAR Collaboration (Physical Review C, 2019)
We report the first measurements of a complete second-order cumulant matrix of net-charge, net-proton, and net-kaon multiplicity distributions for the first phase of the beam energy scan program at the Relativistic Heavy Ion Collider. This includes the centrality and, for the first time, the pseudorapidity window dependence of both diagonal and off-diagonal cumulants in Au+Au collisions at √sNN= 7.7–200 GeV. Within the available acceptance of |η|<0.5, the cumulants grow linearly with the pseudorapidity window. Relative to the corresponding measurements in peripheral collisions, the ratio of off-diagonal over diagonal cumulants in central collisions indicates an excess correlation between net-charge and net-kaon, as well as between net-charge and net-proton. The strength of such excess correlation increases with the collision energy. The correlation between net-proton and net-kaon multiplicity distributions is observed to be negative at √sNN= 200 GeV and change to positive at the lowest collision energy. Model calculations based on nonthermal (UrQMD) and thermal (HRG) production of hadrons cannot explain the data. These measurements will help map the quantum chromodynamics phase diagram, constrain hadron resonance gas model calculations and provide new insights on the energy dependence of baryon-strangeness correlations.
28 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Speckle Interferometry at SOAR in 2018 - Tokovinin, Andrei; Mason, Brian D.; Mendez, Rene A.; Horch, Elliott P.; Briceño, Cesar (The Astronomical Journal, 2019)
The results of speckle interferometric observations at the 4.1 m Southern Astrophysical Research Telescope (SOAR) in 2018 are given, totaling 3097 measurements of 2427 resolved pairs with separations from 11 mas to 5.″9 (median 0.″15, magnitude difference up to 7 mag) and nonresolutions of 624 targets. This work continues our long-term speckle program. Its main goal is to monitor orbital motion of close binaries, including members of high-order hierarchies and Hipparcos pairs in the solar neighborhood. Also, pre-main-sequence stars in the Orion OB1 association were surveyed, resolving 26 out of 118 targets. In addition, we report the discovery of 35 new companions among field visual multiples (some of which are likely optical) and first-time resolutions of another 31 pairs. By combining the measurements given here with the published ones, we computed 76 orbits for the first time and updated orbital elements of 34 visual binaries. Their periods range from 0.65 to 1100 yr, and their quality varies from first tentative solutions of grade 5 to accurate elements of grades 1 and 2. Finally, a list of 53 spurious pairs discovered by various techniques and unresolved at SOAR is given. © 2019. The American Astronomical Society. All rights reserved..
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/174-863-467-125-303, pop00135 tex.type: [object Object]
Keywords: dept.phy; material: machine-readable tables; peer-reviewed

Optical biopsy identification and grading of gliomas using label-free visible resonance Raman spectroscopy. - Zhou, Yan; Liu, Cheng-Hui; Wu, Binlin; Yu, Xinguang; Cheng, Gangge; Zhu, Ke; Wang, Kai; Zhang, Chunyuan; Zhao, Mingyue; Zong, Rui; Zhang, Lin; Shi, Lingyan; et al. (Journal of biomedical optics, 2019)
Glioma is one of the most refractory types of brain tumor. Accurate tumor boundary identification and complete resection of the tumor are essential for glioma removal during brain surgery. We present a method based on visible resonance Raman (VRR) spectroscopy to identify glioma margins and grades. A set of diagnostic spectral biomarkers features are presented based on tissue composition changes revealed by VRR. The Raman spectra include molecular vibrational fingerprints of carotenoids, tryptophan, amide I/II/III, proteins, and lipids. These basic in situ spectral biomarkers are used to identify the tissue from the interface between brain cancer and normal tissue and to evaluate glioma grades. The VRR spectra are also analyzed using principal component analysis for dimension reduction and feature detection and support vector machine for classification. The cross-validated sensitivity, specificity, and accuracy are found to be 100%, 96.3%, and 99.6% to distinguish glioma tissues from normal brain tissues, respectively. The area under the receiver operating characteristic curve for the classification is about 1.0. The accuracies to distinguish normal, low grade (grades I and II), and high grade (grades III and IV) gliomas are found to be 96.3%, 53.7%, and 84.1% for the three groups, respectively, along with a total accuracy of 75.1%. A set of criteria for differentiating normal human brain tissues from normal control tissues is proposed and used to identify brain cancer margins, yielding a diagnostic sensitivity of 100% and specificity of 71%. Our study demonstrates the potential of VRR as a label-free optical molecular histopathology method used for in situ boundary line judgment for brain surgery in the margins.
42 citations (Crossref) [2023-10-31] Place: United States Zhou, Yan. PLA Air Force Medical Center, Department of Neurosurgery, Beijing, China. Liu, Cheng-Hui. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States. Wu, Binlin. Southern Connecticut State University, CSCU Center for Nanotechnology, Physics Department, New Haven, United States. Yu, Xinguang. PLA General Hospital, Department of Neurosurgery, Beijing, China. Cheng, Gangge. PLA Air Force Medical Center, Department of Neurosurgery, Beijing, China. Zhu, Ke. Chinese Academy of Sciences, Institute of Physics, Beijing, China. Wang, Kai. Jilin University, State Key Laboratory of Superhard Materials, Changchun, China. Zhang, Chunyuan. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States. Zhao, Mingyue. PLA Air Force Medical Center, Department of Neurosurgery, Beijing, China. Zong, Rui. PLA General Hospital, Department of Neurosurgery, Beijing, China. Zhang, Lin. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States. Shi, Lingyan. University of California San Diego, Department of Bioengineering, La Jolla, California, United States. Alfano, Robert R. City University of New York, Institute for Ultrafast Spectroscopy and Lasers, Department of Physics, United States.
Keywords: *Biomarkers; Tumor/me [Metabolism]; *Brain Neoplasms/me [Metabolism]; *Brain Neoplasms/pa [Pathology]; *Glioma/me [Metabolism]; *Glioma/pa [Pathology]; *Spectrum Analysis; Raman/mt [Methods]; Amides; Amino acids; Biomarkers; Biomarkers; Tumor; Biomarkers; Tumor/ch [Chemistry]; Biopsy; Brain; Brain Neoplasms; Brain Neoplasms/su [Surgery]; Brain/me [Metabolism]; Brain/pa [Pathology]; Brain/su [Surgery]; Cancer grades; Cancer margins; Carotenoids; Carotenoids/me [Metabolism]; Diseases; Glioblastoma; Glioblastomas; Glioma; Glioma/su [Surgery]; Gliomas; Grading; Histology; Histopathology; Humans; Label free; Label-free; Lipid Metabolism; Margins of Excision; Neoplasm Grading; Nerve Tissue Proteins; Nerve Tissue Proteins/ch [Chemistry]; Nerve Tissue Proteins/me [Metabolism]; Optical Phenomena; Optical biopsies; Optical biopsy; Pigments; Principal Component Analysis; Principal component analysis; Protein Structure; Secondary; Raman spectrometry; Resonance; Resonance Raman; Spectrum Analysis; Raman; Support Vector Machine; Support vector machines; Surgery; Tryptophan; Tryptophan/me [Metabolism]; Tumors; brain; brain tumor; cancer grading; carotenoid; chemistry; dept.phy; glioma; human; light related phenomena; lipid metabolism; metabolism; nerve protein; pathology; peer-reviewed; principal component analysis; procedures; protein secondary structure; support vector machine; surgical margin; tryptophan; tumor marker

Beam energy dependence of (anti-)deuteron production in Au + Au collisions at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2019)
We report the energy dependence of mid-rapidity (anti-)deuteron production in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV, measured by the STAR experiment at the BNL Relativistic Heavy Ion Collider. The yield of deuterons is found to be well described by the thermal model. The collision energy, centrality, and transverse momentum dependence of the coalescence parameter B2 are discussed. We find that the values of B2 for antideuterons are systematically lower than those for deuterons, indicating that the correlation volume of antibaryons is larger than that of baryons at √sNN from 19.6 to 39 GeV. In addition, values of B2 are found to vary with collision energy and show a broad minimum around √sNN=20–40 GeV, which might imply a change of the equation of state of the medium in these collisions.
49 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Detection of planetary and stellar companions to neighboring stars via a combination of radial velocity and direct imaging techniques - Kane, Stephen R.; Dalba, Paul A.; Li, Zhexing; Horch, Elliott P.; Hirsch, Lea A.; Horner, Jonathan; Wittenmyer, Robert A.; Howell, Steve B.; Everett, Mark E.; Butler, R. Paul; Tinney, Christopher G.; Carter, Brad D.; et al. (The Astronomical Journal, 2019)
The sensitivities of radial velocity (RV) surveys for exoplanet detection are extending to increasingly longer orbital periods, where companions with periods of several years are now being regularly discovered. Companions with orbital periods that exceed the duration of the survey manifest in the data as an incomplete orbit or linear trend, a feature that can either present as the sole detectable companion to the host star, or as an additional signal overlain on the signatures of previously discovered companion(s). A diagnostic that can confirm or constrain scenarios in which the trend is caused by an unseen stellar rather than planetary companion is the use of high-contrast imaging observations. Here, we present RV data from the Anglo-Australian Planet Search (AAPS) for 20 stars that show evidence of orbiting companions. Of these, six companions have resolved orbits, with three that lie in the planetary regime. Two of these (HD 92987b and HD 221420b) are new discoveries. Follow-up observations using the Differential Speckle Survey Instrument (DSSI) on the Gemini South telescope revealed that 5 of the 20 monitored companions are likely stellar in nature. We use the sensitivity of the AAPS and DSSI data to place constraints on the mass of the companions for the remaining systems. Our analysis shows that a planetary-mass companion provides the most likely self-consistent explanation of the data for many of the remaining systems.
27 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/016-295-956-723-177, pop00041 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planetary systems; techniques: high angular resolution; techniques: radial velocities

The L 98-59 system: Three transiting, terrestrial-size planets orbiting a nearby M dwarf - Kostov, Veselin B.; Schlieder, Joshua E.; Barclay, Thomas; Quintana, Elisa V.; Colón, Knicole D.; Brande, Jonathan; Collins, Karen A.; Feinstein, Adina D.; Hadden, Samuel; Kane, Stephen R.; Kreidberg, Laura; Kruse, Ethan; et al. (The Astronomical Journal, 2019)
We report the Transiting Exoplanet Survey Satellite (TESS) discovery of three terrestrial-size planets transiting L 98-59 (TOI-175, TIC 307210830)—a bright M dwarf at a distance of 10.6 pc. Using the Gaia-measured distance and broadband photometry, we find that the host star is an M3 dwarf. Combined with the TESS transits from three sectors, the corresponding stellar parameters yield planet radii ranging from 0.8 R ⊕ to 1.6 R ⊕. All three planets have short orbital periods, ranging from 2.25 to 7.45 days with the outer pair just wide of a 2:1 period resonance. Diagnostic tests produced by the TESS Data Validation Report and the vetting package DAVE rule out common false-positive sources. These analyses, along with dedicated follow-up and the multiplicity of the system, lend confidence that the observed signals are caused by planets transiting L 98-59 and are not associated with other sources in the field. The L 98-59 system is interesting for a number of reasons: the host star is bright (V = 11.7 mag, K = 7.1 mag) and the planets are prime targets for further follow-up observations including precision radial-velocity mass measurements and future transit spectroscopy with the James Webb Space Telescope; the near-resonant configuration makes the system a laboratory to study planetary system dynamical evolution; and three planets of relatively similar size in the same system present an opportunity to study terrestrial planets where other variables (age, metallicity, etc.) can be held constant. L 98-59 will be observed in four more TESS sectors, which will provide a wealth of information on the three currently known planets and have the potential to reveal additional planets in the system.
80 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/007-363-095-757-409, pop00014 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; planets and satellites: detection; stars: individual (TIC 307210830; TOI-175); techniques: photometric

Formation and stability of complex metallic phases including quasicrystals explored through combinatorial methods - Wolf, Witor; Kube, Sebastian A.; Sohn, Sungwoo; Xie, Yujun; Cha, Judy J.; Scanley, B. Ellen; Kiminami, Claudio Shyinti; Bolfarini, Claudemiro; Botta, Walter José; Schroers, Jan (Scientific Reports, 2019)
Aluminum-based quasicrystals typically form across narrow composition ranges within binary to quaternary alloys, which makes their fabrication and characterization challenging. Here, we use combinatorial approaches together with fast characterization techniques to study a wide compositional range including known quasicrystal forming compositions. Specifically, we use magnetron co-sputtering to fabricate libraries of ~140 Al-Cu-Fe and ~300 Al-Cu-Fe-Cr alloys. The alloys compositions are measured through automated energy dispersive X-ray spectroscopy. Phase formation and thermal stability are investigated for different thermal processing conditions (as-sputtered and annealed at 400 °C, 520 °C and 600 °C for Al-Cu-Fe libraries; annealed at 600 °C for Al-Cu-Fe-Cr libraries) using automated X-ray diffraction and transmission electron microscopy. In both systems the compositional regions across which the quasicrystalline phase forms are identified. In particular, we demonstrate that the quasicrystalline phase forms across an unusually broad composition range in the Al-Cu-Fe-Cr system. Additionally, some of the considered alloys vitrify during sputtering, which also allows us to study their nucleation behavior. We find that phases with polytetrahedral symmetry, such as the icosahedral quasicrystal and the λ-Al 13 Fe 4 phase, exhibit higher nucleation rates but lower growth rates, as compared to other phases with a lower degree of polytetrahedral order. Altogether, the here used combinatorial approach is powerful to identify compositional regions of quasicrystals. © 2019, The Author(s).
16 citations (Crossref) [2023-10-31] Citation Key Alias: pop00073 tex.type: [object Object]
Keywords: dept.phy

Azimuthal harmonics in small and large collision systems at RHIC top energies - STAR Collaboration (Physical Review Letters, 2019)
The first (vfluc1), second (v2), and third (v3) harmonic coefficients of the azimuthal particle distribution at midrapidity are extracted for charged hadrons and studied as a function of transverse momentum (pT) and mean charged particle multiplicity density ⟨Nch⟩ in U+U (√sNN=193 GeV), Au+Au, Cu+Au, Cu+Cu, d+Au, and p+Au collisions at √sNN=200 GeV with the STAR detector. For the same ⟨Nch⟩, the vfluc1 and v3 coefficients are observed to be independent of the collision system, while v2 exhibits such a scaling only when normalized by the initial-state eccentricity (ϵ2). The data also show that ln(v2/ϵ2) scales linearly with ⟨Nch⟩−1/3. These measurements provide insight into initial-geometry fluctuations and the role of viscous hydrodynamic attenuation on vn from small to large collision systems.
32 citations (Crossref) [2023-10-31] Finch
Keywords: Azimuthal harmonics; Charged hadrons; Charged particle multiplicities; Charged particles; Colliding beam accelerators; Collision systems; Germanium compounds; Gold compounds; Harmonic coefficients; Initial state; Particle distributions; Transverse momenta; dept.phy; peer-reviewed

Collision-energy dependence of pt correlations in Au + Au collisions at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2019)
We present two-particle pt correlations as a function of event centrality for Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 62.4, and 200 GeV at the Relativistic Heavy Ion Collider using the STAR detector. These results are compared to previous measurements from CERES at the Super Proton Synchrotron and from ALICE at the Large Hadron Collider. The data are compared with UrQMD model calculations and with a model based on a Boltzmann-Langevin approach incorporating effects from thermalization. The relative dynamical correlations for Au+Au collisions at √sNN=200 GeV show a power-law dependence on the number of participant nucleons and agree with the results for Pb+Pb collisions at √sNN=2.76TeV from ALICE. As the collision energy is lowered from √sNN=200 to 7.7 GeV, the centrality dependence of the relative dynamical correlations departs from the power-law behavior observed at the higher collision energies. In central collisions, the relative dynamical correlations increase with collision energy up to √sNN=200 GeV in contrast to previous measurements that showed little dependence on the collision energy.
16 citations (Crossref) [2023-10-31]
Keywords: dept.phy; peer-reviewed

Discovery of a compact companion to a nearby star - Kane, Stephen R.; Dalba, Paul A.; Horner, Jonathan; Li, Zhexing; Wittenmyer, Robert A.; Horch, Elliott P.; Howell, Steve B.; Everett, Mark E. (The Astrophysical Journal, 2019)
Radial velocity (RV) searches for exoplanets have surveyed many of the nearest and brightest stars for long-term velocity variations indicative of a companion body. Such surveys often detect high-amplitude velocity signatures of objects that lie outside the planetary mass regime, most commonly those of a low-mass star. Such stellar companions are frequently discarded as false-alarms to the main science goals of the survey, but high-resolution imaging techniques can be employed to either directly detect or place significant constraints on the nature of the companion object. Here, we present the discovery of a compact companion to the nearby star HD 118475. Our Anglo-Australian Telescope RV data allow the extraction of the full Keplerian orbit of the companion, which is found to have a minimum mass of 0.445 M o. Follow-up speckle imaging observations at the predicted time of maximum angular separation rule out a main-sequence star as the source of the RV signature at the 3.3σ significance level, implying that the companion must be a low-luminosity compact object, most likely a white dwarf. We provide an isochrone analysis combined with our data that constrain the possible inclinations of the binary orbit. We discuss the eccentric orbit of the companion in the context of tidal circularization timescales and show that non-circular orbit was likely inherited from the progenitor. Finally, we emphasize the need for utilizing such an observation method to further understand the demographics of white dwarf companions around nearby stars. © 2019. The American Astronomical Society. All rights reserved.
7 citations (Crossref) [2023-10-31]
Keywords: dept.phy; stars: individual (HD 118475); techniques: high angular resolution; techniques: radial velocities; white dwarfs

Distinguish chromophobe renal cell carcinoma and renal oncocytoma based on analysis of multiphoton microscopic images using convolutional neural network - Icaza, Michael; Judd, Nicolas; Jain, Manu; Mukherjee, Sushmita; Wu, Binlin (Optical Biopsy XVII: Toward Real-Time Spectroscopic Imaging and Diagnosis, 2019)
Convolutional neural networks (CNN) are a class of machine learning model that are especially well suited for imagebased tasks. In this study, we design and train a CNN on tissue samples imaged using Multi-Photon Microscopy (MPM) and show that the model can distinguish between chromophobe renal cell carcinoma (chRCC) and oncocytoma. We demonstrate the method to train a model using simple max-pooling vote fusion, and use the model to highlight regions of the input that cause a positive classification. The model can be tuned for higher sensitivity at the cost of specificity with a constant threshold and little impact to accuracy overall. Several numerical experiments were run to measure the model’s accuracy on both image and patient level analysis. Our models were designed with a dropout parameter that biases the model towards higher sensitivity or specificity. Our best performance model, as measured by area under the receiver operating characteristic curve (AUC of ROC, or AUROC) on patient level classification, is measured with a 94% AUROC and 88% accuracy, along with 100% sensitivity and 75% specificity.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/082-242-611-443-764, pop00094
Keywords: Biopsy; Chromophobe renal cell carcinoma; Convolution; Convolutional neural network; Convolutional neural network (CNN); Deep learning; Deep neural networks; Harmonic generation; Image analysis; Kidney tumor; Learning algorithms; Malignancy; Multiphoton microscopy; Multiphoton microscopy (MPM); Neural networks; Nonlinear optics; Renal cell carcinoma; Renal oncocytoma; Second harmonic generation (SHG); dept.phy

Characterization of ZnO and Fe doped ZnO nanoparticles using fluorescence spectroscopy - Singhal, Rahul; Fernando, Mihiri; LeMaire, Peter K.; Wu, Binlin (Oxide-based Materials and Devices X, 2019)
In this study, nanoparticles of pure zinc oxide (ZnO) and ZnO doped with iron of various doping concentrations (Zn_1- xFe_xO) are analyzed using fluorescence spectroscopy. Excitation and emission spectra using various operating wavelengths were collected. Individual spectra and excitation emission matrix were analyzed. Various peaks including strong ultraviolet (UV) emission peaks and strong blue emission peaks that are corresponding to the near-band-edge emission (NBE) and defect emission (DE) peaks were studied based on the peak intensities, peak wavelengths, and NBE peak to defect peak ratios. The Zn_1-xFe_xO materials were also analyzed using X-ray diffraction and optical absorption spectroscopy. The variation in the band gap energy and in the NBE emission energy with dopant concentration was analyzed. A red-shift was observed with the NBE emission peak. The NBE to DE ratio initially increases from pure ZnO to Zn_0.97Fe_0.03O and then decreases as the dopant concentration increases.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/019-994-177-077-315, pop00183
Keywords: Absorption spectroscopy; Band Gap; Band-edge emission (NBE); Band-edge emissions; Defect emission; Defect emission (DE); Defects; Dopant concentrations; Doping concentration; Emission spectroscopy; Energy gap; Excitation and emission spectra; Excitation emission matrices; Fluorescence; Fluorescence spectroscopy; II-VI semiconductors; Iron; Laser radiation; Light absorption; Nanoparticles; Near band edge emissions; Red Shift; Semiconductor doping; X ray diffraction; X-ray diffraction; Zinc oxide; Zinc oxide (ZnO); ZnO nanoparticles; dept.phy

Constraining the initial conditions and temperature dependent viscosity with three-particle correlations in Au+Au collisions - STAR Collaboration (Physics Letters B, 2019)
We present three-particle mixed-harmonic correlations 〈cos⁡(mϕa+nϕb−(m+n)ϕc)〉 for harmonics m,n=1−3 for charged particles in sNN=200 GeV Au+Au collisions at RHIC. These measurements provide information on the three-dimensional structure of the initial collision zone and are important for constraining models of a subsequent low-viscosity quark–gluon plasma expansion phase. We investigate correlations between the first, second and third harmonics predicted as a consequence of fluctuations in the initial state. The dependence of the correlations on the pseudorapidity separation between particles show hints of a breaking of longitudinal invariance. We compare our results to a number of state-of-the art hydrodynamic calculations with different initial states and temperature dependent viscosities. These measurements provide important steps towards constraining the temperature dependent viscosity and longitudinal structure of the initial state at RHIC. © 2018 The Author
2 citations (Crossref) [2023-10-31] Citation Key Alias: pop00019 tex.ids: [object Object] tex.type: [object Object]
Keywords: dept.phy; peer-reviewed

The proton–Ω correlation function in Au + Au collisions at sNN=200GeV - STAR Collaboration (Physics Letters B, 2019)
We present the first measurement of the proton correlation function in heavy-ion collisions for the central (0–40%) and peripheral (40–80%) Au + Au collisions at sNN=200 GeV by the STAR experiment at the Relativistic Heavy-Ion Collider (RHIC). Predictions for the ratio of peripheral collisions to central collisions for the proton correlation function are sensitive to the presence of a nucleon bound state. These predictions are based on the proton interaction extracted from (2+1)-flavor lattice QCD calculations at the physical point. The measured ratio of the proton correlation function between the peripheral (small system) and central (large system) collisions is less than unity for relative momentum smaller than 40 MeV/c. Comparison of our measured correlation ratio with theoretical calculation slightly favors a proton bound system with a binding energy of ∼ 27 MeV.
50 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-293-700-061-567, pop00013 tex.type: [object Object]
Keywords: Correlations; Femtoscopy; NΩ dibaryon; dept.phy; peer-reviewed

Orbits of 14 binaries based on 2018 SOAR speckle observations - Docobo, José A; Gomez, Jorge; Campo, Pedro P; Andrade, Manuel; Horch, Elliott P; Costa, Edgardo; Mendez, Rene A (Monthly Notices of the Royal Astronomical Society, 2019)
New data obtained during the 2018 March-April speckle run at the 4.1 m Southern Astrophysical Research (SOAR) telescope located at Cerro Pachón (Chile) allowed us to recalculate the orbits of the following visual binaries: WDS 06478+0020 (STT 157),WDS 07003-2207 (FIN 334Aa,Ab), WDS 07013-0906 (A 671), WDS 10174-5354 (CVN 16Aa,Ab), WDS 12155-3106 (RST 1658),WDS 12572+0818 (FIN 380),WDS 13044-1316 (HU 642),WDS 14243-3838 (RST 1785), WDS 16094-3103 (I 557), WDS 17115-1630 (HU 169), WDS 17119-0151 (LPM 629),WDS 17563 + 0259 (A 2189),WDS 18464-2755 (RST 2073), and WDS 19035-6845 (FIN 357). All but three of them are Southern stars. The recently published Gaia parallaxes were used to calculate the total mass of each of these systems, despite the fact that, in a few cases, only Hipparcos parallaxes were available. For two binaries, A 671 and RST 2073, there are no parallax data. However, in these cases, the masses deduced from the dynamical parallaxes provided relevant information. In addition, we also present the first orbit for each of three systems: HU 642, RST 1785, and RST 2073, using speckle measurements. Finally, using the dynamical parallaxes given by these orbits, we have been able to calculate the luminosity of these systems. Said luminosities allow us to indicate an approximate age for each of the components of the system, situating them within the HR diagram. © 2018 The Author(s) Published by Oxford University Press on behalf of the Royal Astronomical Society.
7 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/024-727-074-773-961, pop00143 tex.type: [object Object]
Keywords: Techniques: high angular resolution - astrometry - binaries; Visual - stars: fundamental parameters; dept.phy; peer-reviewed

Observations of binary stars with the Differential Speckle Survey Instrument. VIII. Measures of metal-poor and triple stars from 2015 to 2018 - Horch, Elliott P.; Tokovinin, Andrei; Weiss, Samuel A.; Löbb, János; Casetti-Dinescu, Dana I.; Granucci, Nicole M.; Hess, Nicole M.; Everett, Mark E.; van Belle, Gerard T.; Winters, Jennifer G.; Nusdeo, Daniel A.; Henry, Todd J.; et al. (The Astronomical Journal, 2019)
We present 248 speckle observations of 43 binary and 19 trinary star systems chosen to make progress in two main areas of investigation: the fundamental properties of metal-poor stars and star formation mechanisms. The observations were taken at the Gemini North and South telescopes during the period 2015 July to 2018 April, mainly with the Differential Speckle Survey Instrument but also with a few early results from the new 'Alopeke speckle camera at Gemini North. We find that the astrometry and photometry of these observations as a whole are consistent with previous work at Gemini. We present five new visual orbits for systems important in understanding metal-poor stars, three of which have orbital periods of less than 4 yr, and we indicate the degree to which these and future observations can impact our knowledge of stellar properties and star formation. In particular, we find a decrease in mass at fixed spectral type for metal-poor stars versus their solar-metallicity analogs that is consistent with predictions that are made from current stellar models. © 2019. The American Astronomical Society. All rights reserved..
19 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/073-502-692-786-428, pop00025 tex.type: [object Object]
Keywords: binaries: visual; dept.phy; peer-reviewed; stars: individual; techniques: high angular resolution; techniques: interferometric; techniques: photometric

Visible resonance raman spectroscopy in human brain tissues - Zhou, Yan; Liu, Cheng-hui; Zhu, Ke; Wu, Binlin; Yu, Xinguang; Alfano, Robert R. (Neurophotonics and Biomedical Spectroscopy, 2019)
This chapter first reviews the research and applications of nonresonance and resonance Raman spectroscopy for analysis of human brain normal and abnormal tissues. Next, special emphasis is made on our recent achievements of visible resonance Raman (VRR) technique in primary human brain tumor disease investigation and diagnosis. Visible resonance Raman (VRR) spectroscopy technique uses excitation of visible light (532 nm) to evaluate the resonant and nonresonant molecular vibrational modes in biological tissues. The VRR signal intensities are enhanced by two to three orders of magnitude for faster use in medical applications in quasi real time. VRR opens up a new stainless “molecular optics based histopathology” diagnosis approach. © 2019 Elsevier Ltd. All rights reserved.
Keywords: Brain cancer margin assessment; Glioblastoma multiforme (GBM); Glioblastoma multiforme (gbm); Gliomas; Meninges; Optical biopsy; Visible resonance Raman (VRR) spectroscopy; Visible resonance raman (vrr) spectroscopy; Wavelength 532 nm; Wavelength 532nm; dept.phy

The Origins of Young Stars in the Direction of the Leading Arm of the Magellanic Stream: Abundances, Kinematics, and Orbits. - Zhang, Lan; Casetti-Dinescu, Dana I; Bidin, Christian Moni; Mendez, Rene A; Girard, Terrence M; Vieira, Katherine; Korchagin, Vladimir I; van Altena, William F; Zhao, Gang (The Astrophysical journal, 2019)
We explore the origins of the young B-type stars found by Casetti-Dinescu et al. (2014) at the outskirts of the Milky-Way disk in the sky region of Leading Arm of the Magellanic Stream. High-resolution spectroscopic observations made with the MIKE instrument on the Magellan Clay 6.5m telescope for nine stars are added to the previous sample analyzed by Zhang et al. (2017). We compile a sample of fifteen young stars with well-determined stellar types, ages, abundances and kinematics. With proper motions from Gaia DR2 we also derive orbits in a realistic Milky-Way potential. We find that our previous radial-velocity selected LA candidates have substantial orbital angular momentum. The substantial amount of rotational component for these stars is in contrast with the near-polar Magellanic orbit, thus rendering these stars unlikely members of the LA. There are four large orbital-energy stars in our sample. The highest orbital-energy one has an age shorter than the time to disk crossing, with a birthplace z = 2.5 kpc and R GC ~ 28 kpc. Therefore, the origin of this star is uncertain. The remaining three stars have disk runaway origin with birthplaces between 12 and 25 kpc from the Galactic center. Also, the most energetic stars are more metal poor ([Mg/H] =-0.50 +/- 0.07) and with larger He scatter (sigma [He/H] = 0.72) than the inner disk ones ([Mg/H] = 0.12 +/- 0.36, sigma [He/H] = 0.15). While the former group's abundance is compatible with that of the Large Magellanic Cloud, it could also reflect the metallicity gradient of the MW disk and their runaway status via different runaway mechanisms.
4 citations (Crossref) [2023-10-31] Place: United States Zhang, Lan. Key Lab of Optical Astronomy, National Astronomical Observatories, CAS, 20A Datun Road, Chaoyang District, 100012 Beijing, China. Casetti-Dinescu, Dana I. Department of Physics, Southern Connecticut State University, 501 Crescent St., New Haven, CT 06515, USA. Casetti-Dinescu, Dana I. Astronomical Institute of the Romanian Academy, str. Cutitul de Argint 5, Bucharest, Romania. Casetti-Dinescu, Dana I. Radiology and Biomedical Imaging, Yale School of Medicine, 300 Cedar Street, New Haven 06519, USA. Bidin, Christian Moni. Instituto de Astronomia, Universidad Catolica del Norte, Av. Angomos 0610, Antofagasta, Chile. Mendez, Rene A. Departamento de Astronomia, Universidad de Chile, Casilla 36-D, Santiago, Chile. Girard, Terrence M. 14 Dunn Rd, Hamden, Connecticut, CT 06518, USA. Vieira, Katherine. Centro de Investigaciones de Astronomia, Apartado Postal 264, Merida 5101-A, Venezuela. Korchagin, Vladimir I. Institute of Physics, Southern Federal University, Stachki st/194, 344090, Rostov-on-Don, Russia. van Altena, William F. Astronomy Department, Yale University, 260 Whitney Ave., New Haven, CT 06511, USA. Zhao, Gang. Key Lab of Optical Astronomy, National Astronomical Observatories, CAS, 20A Datun Road, Chaoyang District, 100012 Beijing, China.
Keywords: dept.phy; stars: abundances; stars: early-type; stars: kinematics and dynamics

Combined spatial frequency spectroscopy analysis with visible resonance Raman for optical biopsy of human brain metastases of lung cancers - Zhou, Yan; Liu, Cheng-Hui; Pu, Yang; Wu, Binlin; Nguyen, Thien An; Cheng, Gangge; Zhou, Lixin; Zhu, Ke; Chen, Jun; Li, Qingbo; Alfano, Robert R. (Journal of Innovative Optical Health Sciences, 2019)
The purpose of this study is to examine optical spatial frequency spectroscopy analysis (SFSA) combined with visible resonance Raman (VRR) spectroscopic method, for the first time, to discriminate human brain metastases of lung cancers adenocarcinoma (ADC) and squamous cell carcinoma (SCC) from normal tissues. A total of 31 label-free micrographic images of three types of brain tissues were obtained using a confocal micro-Raman spectroscopic system. VRR spectra of the corresponding samples were synchronously collected using excitation wavelength of 532[Formula: see text]nm from the same sites of the tissues. Using SFSA method, the difference in the randomness of spatial frequency structures in the micrograph images was analyzed using Gaussian function fitting. The standard deviations, [Formula: see text] calculated from the spatial frequencies of the micrograph images were then analyzed using support vector machine (SVM) classifier. The key VRR biomolecular fingerprints of carotenoids, tryptophan, amide II, lipids and proteins (methylene/methyl groups) were also analyzed using SVM classifier. All three types of brain tissues were identified with high accuracy in the two approaches with high correlation. The results show that SFSA–VRR can potentially be a dual-modal method to provide new criteria for identifying the three types of human brain tissues, which are on-site, real-time and label-free and may improve the accuracy of brain biopsy.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/037-734-581-386-058, zhouCombinedSpatialFrequency2019a
Keywords: Amides; Amino acids; Article; Biopsy; Brain; Diseases; Histology; Human brain; Image analysis; Metastatic lung cancer; Pathology; Raman spectrometry; Resonance; Resonance Raman; Spatial frequency; Spatial frequency spectroscopy analysis (SFSA); Spatial variables measurement; Spectroscopic analysis; Spectrum analysis; Support vector machines; Tissue; accuracy; amide; brain metastasis; brain tissue; cancer classification; carbene; carotenoid; controlled study; dept.phy; diagnostic test accuracy study; excitation; fatty acid; high density lipoprotein; histopathology; human; human brain; human tissue; lipid; low density lipoprotein; lung adenocarcinoma; metastatic lung cancer; methyl group; molecular imaging; peer-reviewed; photomicrograph image; sensitivity and specificity; spatial frequency spectroscopy analysis; spectroscopy; squamous cell lung carcinoma; support vector machine; support vector machine (SVM); tryptophan; visible resonance Raman (VRR); visible resonance Raman spectroscopy

High performance logic and circuits for high-speed electronic systems - Jain, F; Broadbridge, C; Gherasimova, M; Tang, H (World Scientific Publishing Co., 2019)
In this volume, we have put together papers spanning a broad range from the area of modeling of strain and misfit dislocation densities, microwave absorption characteristics of nanocomposites, to X-ray diffraction studies. Specific topics in this volume include: Modeling of strain relaxation and defect dynamics in buffer layers for semiconductor devices fabricated on lattice-mismatched substrates, which enables technology for advanced computer chips, multi-junction solar cells, detectors, and microwave transistors. Physical Unclonable Functions (PUFs) are probabilistic circuit primitives that extract randomness from the physical characteristics of devices. One of the papers outlines PUF design based on resistor and capacitor variations for low pass filters (LoPUF). Spatial wavefunction switching (SWS) FETs, which can process 2-bits per FET using CMOS-SWS logic, thus enabling multivalued logic (MVL) and compact DRAMs. Perimeter gated single-photon avalanche diode (PGSPAD). The applied voltage at the gate terminal modulates the electric field, making it uniform throughout the junction. This gating technique is an efficient method to prevent premature edge breakdown, one of the major problems in operating avalanche photodiodes implemented in CMOS process. In summary, papers selected in this volume cover various aspects of high performance logic and circuits for high-speed electronic systems. © 2019 by World Scientific Publishing Co. Pte. Ltd. All rights reserved.
Keywords: dept.phy

Phase selection motifs in High Entropy Alloys revealed through combinatorial methods: Large atomic size difference favors BCC over FCC - Kube, Sebastian A; Sohn, Sungwoo; Uhl, David; Datye, Amit; Mehta, Apurva; Schroers, Jan (Acta Materialia, 2019)
High Entropy Alloys are inherently complex and span a vast composition space, making their research and discovery challenging. Developing quantitative predictions of their phase selection requires a large quantity of consistently determined experimental data. Here, we use combinatorial methods to fabricate and characterize 2478 quinary alloys based on Al and transition metals. All data are publicly available at http://materialsatlasproject.org/. Phase selection can be predicted for considered alloys when combining the content of FCC/BCC elements and the constituents’ atomic size difference. Mining our data reveals that High Entropy Alloys with increasing atomic size difference prefer BCC structure over FCC. This preference is typically overshadowed by other selection motifs, which dominate during close-to-equilibrium processing. Not suggested by the Hume-Rothery rules, this preference originates from the ability of the BCC structure to accommodate a large atomic size difference with lower strain energy penalty which can be practically only realized in High Entropy Alloys. © 2019 Acta Materialia Inc.
136 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/048-312-417-394-434 tex.type: [object Object]
Keywords: Aluminum alloys; Atomic size difference; Atomic sizes; Atoms; Combinatorial method; Combinatorial sputtering; Composition space; Crystal structure; Entropy; High entropy alloys; Hume-Rothery rules; Phase selection; Quantitative prediction; Strain energy; Transition metals; dept.phy; peer-reviewed

Study of MnO2-Graphene Oxide nanocomposites for supercapacitor applications - Singhal, Rahul; Fagnoni, Justin; Thorne, David; LeMaire, Peter K.; Martinez, Xavier; Zhao, Chen; Gupta, Ram K.; Uhl, David; Scanley, Ellen; Broadbridge, Christine C.; Manivannan, Mani; Pandey, Rishikesh (MRS Advances, 2019)
Graphene oxide (GO)/MnO2 nanocomposites were synthesized by adding KMnO4 in a solution of water and ethanol (3:1), containing 10 mg of GO. Brown precipitates were obtained after a continuous stirring for 1 hr. The precipitates were then washed with deionized water (DI) water and dried to obtain the MnO2-GO nanocomposites. Pure MnO2 was also synthesized using the same method without GO for the comparison. X-ray diffraction pattern confirm δ-MnO2 type of MnO2 with birnessite type MnO2 structure. The TEM images show the average diameter of MnO2 nanorods as 15 nm. Electrochemical characterizations were carried out in an aqueous solution of 3M KOH. Charge-discharge studies were carried out between 1A/g to 20 A/g current range. The MnO2-GO nanocomposites showed improved electrochemical performances. The capacitance of MnO2 and MnO2-GO electrodes was found to be as 300 F/g, and 350 F/g, respectively at a current of 0.5 A/g. © 2019 Materials Research Society.
6 citations (Crossref) [2023-10-31]
Keywords: Average diameter; Charge-discharge; Continuous stirrings; Current range; Deionized water; Electric discharges; Electrochemical characterizations; Electrochemical performance; Energy storage; Graphene; Graphene oxide nanocomposites; Manganese oxide; Nanocomposites; Nanorods; Potassium hydroxide; Raman spectroscopy; Supercapacitor; Supercapacitor application; X ray diffraction; dept.phy; energy storage; graphene; peer-reviewed; x-ray diffraction (XRD)

Speckle observations and orbits of multiple stars. - Tokovinin, Andrei; Everett, Mark E; Horch, Elliott P; Torres, Guillermo; Latham, David W (Astronomical Journal, 2019)
We report results of speckle-interferometric monitoring of visual hierarchical systems using the newly commissioned instrument NN-EXPLORE Exoplanet and Stellar Speckle Imager at the 3.5 m WIYN telescope. During one year, 390 measurements of 129 resolved subsystems were made, while some targets were unresolved. Using our astrometry and archival data, we computed 36 orbits (27 for the first time). Spectro-interferometric orbits of seven pairs are determined by combining positional measurements with radial velocities measured, mostly, with the Center for Astrophysics digital speedometers. For the hierarchical systems HIP 65026 (periods 49 and 1.23 yr) and HIP 85209 (periods 34 and 1.23 yr) we determined both the inner and the outer orbits using astrometry and radial velocities and measured the mutual orbit inclinations of 11.°3 ± 1.°0 and 12.°0 ± 3.°0, respectively. Four bright stars are resolved for the first time; two of those are triple systems. Several visual subsystems announced in the literature are shown to be spurious. We note that subsystems in compact hierarchies with outer separations less than 100 au tend to have less eccentric orbits compared to wider hierarchies. © 2019. The American Astronomical Society. All rights reserved..
13 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/097-296-370-783-044 tex.type: [object Object]
Keywords: dept.phy; peer-reviewed; ⛔ No DOI found